Hyperfine excitation of SH+ by H - Lique, Francois; Zanchet, Alexandre; Bulut, Niyazi; Goicoechea, Javier R.; Roncero, Octavio (Edp Sciences S A, 2020)
Context. SH+ is a surprisingly widespread molecular ion in diffuse interstellar clouds. There, it plays an important role by triggering the sulfur chemistry. In addition, SH+ emission lines have been detected at the UV-illuminated edges of dense molecular clouds, so-called photo-dissociation regions (PDRs), and toward high-mass protostars. An accurate determination of the SH+ abundance and of the physical conditions prevailing in these energetic environments relies on knowing the rate coefficients of inelastic collisions between SH+ molecules and hydrogen atoms, hydrogen molecules, and electrons.Aims. We derive SH+-H fine and hyperfine-resolved rate coefficients from recent quantum calculations for the SH+-H collisions, including inelastic, exchange, and reactive processes.Methods. The method we used is based on the infinite-order sudden approach.Results. State-to-state rate coefficients between the first 31 fine levels and 61 hyperfine levels of SH+ were obtained for temperatures ranging from 10 to 1000 K. Fine-structure resolved rate coefficients present a strong propensity rule in favor of Delta j=Delta N transitions. The Delta j=Delta F propensity rule is observed for the hyperfine transitions.Conclusions. The new rate coefficients will help significantly in the interpretation of SH+ spectra from PDRs and UV-irradiated shocks where the abundance of hydrogen atoms with respect to hydrogen molecules can be significant.
Keywords: molecular data; molecular processes; radiative transfer; methods: laboratory: molecular